2002
DOI: 10.1128/iai.70.5.2721-2724.2002
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunization with Bovine Milk Containing Antibodies to a Cell Surface Protein Antigen-Glucosyltransferase Fusion Protein Protects Rats against Dental Caries

Abstract: Cell surface protein antigen (PAc) and glucosyltransferases (GTF) of Streptococcus mutans are major colonization factors of the organism. We prepared bovine milk containing antibodies against a fusion of the saliva-binding alanine-rich region of PAc with the glucan-binding domain of GTF-I. This study examined the effect of the immune milk on the cariogenicity of S. mutans in a rat model. Concentrated immune milk was fed to rats once a day for 55 days. The group that received immune milk had significantly less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
(21 reference statements)
0
19
1
1
Order By: Relevance
“…Recent studies by others using a similar fusion protein, termed "PAcA-GB," have shown that bovine milk containing antibodies against the fusion protein was effective in controlling the recolonization of S. mutans in the oral cavity of humans (37). Furthermore, passive immunization of rats with bovine milk containing antibodies against the PAcA-GB fusion protein was shown to protect against S. mutans induced dental caries in a rat model (25). However, these investigators did not compare the effectiveness of antibodies to the chimeric protein to that of the antibodies to each component.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by others using a similar fusion protein, termed "PAcA-GB," have shown that bovine milk containing antibodies against the fusion protein was effective in controlling the recolonization of S. mutans in the oral cavity of humans (37). Furthermore, passive immunization of rats with bovine milk containing antibodies against the PAcA-GB fusion protein was shown to protect against S. mutans induced dental caries in a rat model (25). However, these investigators did not compare the effectiveness of antibodies to the chimeric protein to that of the antibodies to each component.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Koga and colleagues (Mitoma et al, 2002) have demonstrated passive protection of rats against dental caries using milk produced from cows vaccinated with a Pac-Gtf fusion protein antigen. This suggests the possibility of using foods containing antibodies as a means of passively protecting children against dental caries.…”
Section: (B) Vaccines Against Oral Diseasesmentioning
confidence: 99%
“…CCL19 is a high-affinity functional ligand for CCR7, the receptor molecule expressed on mature DCs [8,9] . It has been demonstrated that CCL19 and CCR7 play an important role in DC homing to lymphoid tissues [15][16][17][18][19] .…”
Section: Wwwchinapharcom Yan Yh Et Almentioning
confidence: 99%
“…Following intramuscular injection of a plasmid DNA vaccine, the encoded gene is thought to be expressed in transfected myocytes at the site of inoculation [4] , as well as in a small number of dendritic cells (DCs) [5][6][7][8] . DCs capture the antigens expressed by transfected cells, process, and then present them to T cells in secondary lymphoid organs where naive www.chinaphar.com Yan YH et al Acta Pharmacologica Sinica npg T cells are activated [9] . In this process, DCs undergo radical changes from immature phagocytic precursor cells to potent antigen-presenting cells (APCs) and upregulate receptors for constitutive chemokines, such as C-C chemokine receptor type 7 (CCR7) [10,11] .…”
Section: Introductionmentioning
confidence: 99%